Bio-physicochemical study for glutinous and nonglutinous rice with genetic diversity of Bangladeshi rice germplasm - Nilufa Ferdous; M. Zakir Hossain Hawlader; Sunil Kumar Biswas; Habibul Bari Shozib; Md. Anwarul Haque; Muhammad Ali Siddiquee; M. Akhlasur Rahman; Shakir Hosen (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2020)
Glutinous rice is popularly known as sticky rice in Japan, Korea, China, Thailand, Philippine, Malaysia, Indonesia and some other countries. People of those countries preferably take it as cooked rice and various kind of processing food. Information on physicochemical properties of this glutinous rice is available in those countries, while in Bangladesh, there is no information about physicochemical properties and polymorphisms of the glutinous rice. Therefore, the study was conducted to characterize the physicochemical properties and polymorphisms of glutinous rice varieties. A set of 36 rice germplasms were used in this study. All parameters of physicochemical properties were analyzed as per laboratory manual of Grain and Nutritional Quality division of BRRI as well as molecular trait was analyzed as per laboratory manual of Biochemistry and Molecular Biology Department under university of Dhaka. All rice germplasm were analyzed by the cleaved amplified polymorphic sequence marker RM190F-GBSSW2R/AccI for determination of G/T single nucleotide polymorphism (SNP) of the Waxy gene. In this study, 7 glutinous rice samples have shown T polymorphism (AGTTATA sequence) whereas 29 nonglutinous rice germplasms have shown G polymorphism (AGGTATA sequence). The range of amylose content of all glutinous rice (T polymorphism) varied from 5% to 8.4%, whereas nonglutinous rice (G polymorphism) varied from 11% to 29%.